2022
DOI: 10.3390/ijms23094495
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Deregulation of Protein Tyrosine Kinase 6 Promotes Carcinogenesis of Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) accounts for over 90% of oral cancers and causes considerable morbidity and mortality. Epigenetic deregulation is a common mechanism underlying carcinogenesis. DNA methylation deregulation is the epigenetic change observed during the transformation of normal cells to precancerous and eventually cancer cells. This study investigated the DNA methylation patterns of PTK6 during the development of OSCC. Bisulfite genomic DNA sequencing was performed to determine the PTK6 methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Studies have reported the potential of IL24 as a diagnostic marker in ovarian tumor subtypes, supporting its relevance in subtype-speci c diagnosis [17,18]. PTK6, also known as Protein Tyrosine Kinase 6, is another gene of interest that has been implicated in cancer pathogenesis [19][20][21]. Previous investigations have demonstrated the correlation between PTK6 expression and cancer stages in ovarian carcinoma, suggesting its potential as a staging biomarker for disease prognosis and management [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have reported the potential of IL24 as a diagnostic marker in ovarian tumor subtypes, supporting its relevance in subtype-speci c diagnosis [17,18]. PTK6, also known as Protein Tyrosine Kinase 6, is another gene of interest that has been implicated in cancer pathogenesis [19][20][21]. Previous investigations have demonstrated the correlation between PTK6 expression and cancer stages in ovarian carcinoma, suggesting its potential as a staging biomarker for disease prognosis and management [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…Most importantly, analysis of the four genes using the REACTOME database associated their altered expression with key cancer-related molecular pathways. Namely, pathways related to PTK6 (Protein Tyrosine Kinase 6 or Brk), whose activity and regulation are strongly associated with multiple cancers, like colon [26] and breast cancer [32,33], oral squamous cell carcinoma [34] or hepatocellular carcinoma [35] by different mechanisms. Of note, one of these mechanisms relates to the appearance of a splicing isoform (Alt Brk) that may act by preventing tumor progression [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…1 It is the most prevalent type of head and neck cancer in the world. 2 The overall 5-year survival rate has not significantly increased over the previous decades despite continued therapeutic advances, making it as a serious global health problem. 3 It is essential to identify biomarkers that can precisely predict prognosis in order to provide more effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Oral cancer is a general term for malignant tumors that form in different parts of the oral cavity and generally affect the tongue, floor of the mouth, gingiva, buccal mucosa, palate, and lips 1 . It is the most prevalent type of head and neck cancer in the world 2 . The overall 5‐year survival rate has not significantly increased over the previous decades despite continued therapeutic advances, making it as a serious global health problem 3 .…”
Section: Introductionmentioning
confidence: 99%